Problem Identification and Policy Network on Law Number 21 Year 2023 on National Capital City - Rivandi, Sultan; Pramono, Sidik (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research aims to analyze the identification of issues during the policy formulation process of law number 21 of 2023 concerning the national capital and to conduct a network analysis of policy formulation pertaining to the same law. The research employs a descriptive method with a qualitative approach, utilizing data collection techniques through interviews and literature studies. The findings indicate several identified issues, including environmental sustainability, long-term financing, and governance efficiency. The government has implemented several improvements, such as ensuring legal certainty, long-term financing, flexible and responsive regulations to change, and the sustainability of national capital development. This process reflects the government's efforts to address shortcomings in previous policies, particularly regarding the strengthening of legal and socio-cultural positions. Nevertheless, in areas related to economic aspects, funding management, and environmental issues, there is limited public criticism or input accommodated. Furthermore, the interaction patterns among actors (policy networks) indicate an increase in public participation space, although the central government's dominance as an aggregator of interests still significantly influences other actors in the policy formulation process, leading to a closure in policy options. The policy formulation process of law number 21 of 2023 concerning the national capital has not achieved a balance among the stakeholders involved.